Comparison of european Trichobilharzia species based on ITS1 and ITS2 sequences - Dvorák, J; Vanácová, S; Hampl, V; Flegr, J; Horák, P (Parasitology, 2002)
Schistosomes are parasites of considerable medical and veterinary importance and, therefore, all aspects of their biology have been intensively studied. In contrast, our knowledge of species of the largest genus, Trichobilharzia, is insufficient. Because morphological characterization of Trichobilharzia species provides a limited number of criteria for species determination, molecular data are required. In the present paper, we sequenced internal transcribed spacers ITS1 and ITS2, and 5.8S ribosomal RNA (rRNA) genes of 3 European Trichobilharzia species (T. regenti, T. szidati and T. franki). We showed that ITS1 and ITS2 sequences can be used in species identification. Repetitive elements were found in ITS1 of all 3 Trichobilharzia species; their number and length varied depending on the species. Phylogenetic analysis showed that the visceral T. franki is more related to the nasal T. regenti, than to the visceral T. szidati. The newly designed primer, which is specific for T. regenti, might be used as a tool for diagnosis of this potential pathogen.
Keywords: Base Sequence; Schistosomatidae; Sequence Homology, Nucleic Acid; fylogeneze; polymerázová řetězová reakce; sekvenční homologie nukleových kyselin; mezerníky ribozomální DNA; sekvence nukleotidů; Molecular Sequence Data; Evropa; DNA, Ribosomal Spacer; Animals; zvířata; Europe; RNA, Ribosomal, 5.8S; Phylogeny; molekulární sekvence - údaje; RNA ribozomální 5.8S; Polymerase Chain Reaction